HUBUNGAN MINAT MEMBACA, FASILITAS ORANG TUA, DAN PEMBERIAN TUGAS MEMBACA DENGAN KEMAMPUAN MEMBACA PEMAHAMAN SISWA - Romafi, Romafi; Musfiroh, Tadkiroatun (LingTera, 2015)
Penelitian ini  bertujuan  untuk mengungkapkan hubungan minat membaca, fasilitas orang tua, dan pemberian tugas membaca di sekolah dengan kemampuan membaca pemahaman siswa kelas VIII SMP negeri di Kabupaten Brebes. Penelitian ini merupakan penelitian  ex post facto dengan populasi seluruh siswa kelas VIII SMPN Negeri di Kabupaten Brebes. Sampel ditentukan lewat teknik stratified random sampling berdasarkan nilai akreditasi sekolah A, B, dan C. Data dianalisis menggunakan analisis deskriptif. Uji prasyarat dilakukan dengan uji normalitas, linieritas, dan homogenitas. Pengujian hipotesis dilakukan dengan analisis korelasi sederhana, korelasi parsial, dan korelasi ganda. Hasil penelitian ini adalah minat membaca (X1), fasilitas orang tua (X2), dan pemberian tugas membaca di sekolah (X3) berhubungan positif dan signifikan dengan kemampuan membaca pemahaman (Y) pada siswa kelas VIII SMP negeri di Kabupaten Brebes (ry1-23=0,294, ry2-13=0,302, ry3-12=0,255, Ry-123= 0,489). Kata kunci: minat membaca, fasilitas orang tua, pemberian tugas membaca, kemampuan membaca pemahaman   THE RELATIONSHIP AMONG INTEREST IN READING, PARENTS’ FACILITIES, AND GIVING TASKS IN SCHOOLS WITH THE READING COMPREHENSION Abstract This research was aimed to reveal the relationship among interest in reading (X1), parents’ facilities (X2) and giving task of reading in school (X3) jointly with the  reading comprehension (Y) in the students of the eighth grade of State Junior High School (SMP) in Brebes Regency. This was an ex post facto research with the population of all eighth grade students in Brebes Regency. The samples were determined by a stratified random sampling technique based on school accreditation strata of A, B and C. Data was analyzed using a descriptive analysis. The pre-condition test was conducted by normality, linearit, and homogeneity tests. The hypothesis examination was conducted by a simple correlation, partial correlation, and multiple correlations. This research result was  interest in reading (X1), parents’ facilities (X2) and giving task of reading in school (X3) jointly positively and significantly related to the reading comprehension (Y) in the students of the eighth grade of State Junior High School (SMP) in Brebes Regency (ry1-23=0,294, ry2-13=0,302, ry3-12=0,255, Ry-123= 0,489). Keywords: interest in reading, parents’ facilities, giving task in school, reading comprehension